Calculation of the resistance of an unequal span steel substructure against progressive collapse based on the component method. (1st March 2019) - Meng, Bao; Zhong, Weihui; Hao, Jiping; Song, Xiaoyan; Tan, Zheng
Highlights: An unequal span steel substructure is analysed for progressive collapse resistance. The top-seat angle with a double web angle connection is modelled using the component method. A set of explicit equations for progressive collapse resistance are derived. A numerical model is evaluated using the component model of the TSDWA connection. The equations and model show good agreement with previous test results. Abstract: The rapid quantitative assessment of a structure's resistance is critical to the structural design process in order to prevent the occurrence of progressive collapse. In this study, a three-bar component model of a top-seat angle with a double web angle connection was constructed based on the component method by dividing and simplifying its geometry. The proposed component model was then applied to a model of an unequal span substructure. An explicit calculation method and a numerical simulation method were proposed to describe the nonlinear static responses of the unequal span substructure under a scenario of interior column failure. These two methods were carefully validated against previously collected experimental data and were determined to accurately reflect the main responses of the structure, including the load–displacement relationship, development of internal forces, and deformation behaviour. The explicit calculation procedure, conducted using a step-by-step process in an Excel spreadsheet, was successfully applied to rapidly analyse and quantitatively evaluate the resistance of the unequal span steel substructure, which will lay the foundation for the resistance prediction and performance analysis of the whole structure against progressive collapse.